Statistical physics. Part 1 - Landau, L. D. 1908-1968 (Elsevier Butterworth Heinemann, 1980)
A lucid presentation of statistical physics and thermodynamics which develops from the general principles to give a large number of applications of the theory.
Published in 2 parts.
Includes index.
Keywords: Statistical mechanics.; elektronické knihy; electronic books